2014 ESC GUIDELINES ON DIAGNOSIS AND MANAGEMENT OF HYPERTROPHIC CARDIOMYOPATHY - Perry M. Elliott; Aris Anastasakis; Michael A. Borger; Martin Borggrefe; Franco Cecchi; Philippe Charron; Albert Alain Hagege; Antoine Lafont; Giuseppe Limongelli; Heiko Mahrholdt; William J. McKenna; Jens Mogensen; et al. (Российский кардиологический журнал)
.